Patient satisfaction for telemedicine health services in the era of COVID-19 pandemic: A systematic review - Kaur, Karuna Nidhi; Niazi, Farah; Thakur, Ruchi; Saeed, Shazina; Rana, Shweta; Singh, Harpreet (Frontiers in Public Health, 2022)
ABSTRACT INTRODUCTION: In the year 2019, the whole world witnessed the COVID-19 pandemic. The pandemic has negatively impacted the healthcare delivery system. This has risen the necessity among health systems across the world to deliver healthcare services through telemedicine. This systematic review would assess the level of patient satisfaction for telemedicine health services during the time of COVID-19 pandemic. METHODOLOGY: The literature search was conducted in June 2022 using “PUBMED”, “Google Scholar” and “Embrace” databases. Total eight articles were included. ROBVIS Analysis was performed for the assessment of bias. Descriptive statistics were performed using Microsoft Excel. RESULTS: All included studies were conducted in seven countries/states: India(n=2), Philippines(n=1), Saudi Arabia(n=1), UAE(n=1), Los Angeles(n=1), Iran(n=1), New York(n=1). Most used telemedicine tools were voice call, video call and messaging/E-mail. Maximum patients used video for consultation (5 out of 9 studies) followed by voice call (4 out of 8 studies), messaging/ E-mails (2 out of 8 studies) and other telemedicine Apps (2 out of 8 studies). Overall, level of satisfaction was found highest amongst studies conducted in developed countries/states such as New York (94.87%), Los Angeles (82.7%), UAE (81%) and South Arabia (77.9%) in contrast to the studies conducted in developing countries which includes Philippines (82%), India (73.9%; 51.3%) and Iran (43.43%). CONCLUSION: Most of the participants were found to be satisfied with the quality of telemedicine they were offered. This systematic review will help to improve telemedicine services which will eventually improve the healthcare delivery system.